Solve for b 3=-5/6*(-5)+b

Math
3=-56⋅(-5)+b
Rewrite the equation as -56⋅(-5)+b=3.
-56⋅(-5)+b=3
Simplify each term.
Tap for more steps…
Move the negative in front of the fraction.
-56⋅-5+b=3
Multiply -56⋅-5.
Tap for more steps…
Multiply -5 by -1.
5(56)+b=3
Combine 5 and 56.
5⋅56+b=3
Multiply 5 by 5.
256+b=3
256+b=3
256+b=3
Move all terms not containing b to the right side of the equation.
Tap for more steps…
Subtract 256 from both sides of the equation.
b=3-256
To write 3 as a fraction with a common denominator, multiply by 66.
b=3⋅66-256
Combine 3 and 66.
b=3⋅66-256
Combine the numerators over the common denominator.
b=3⋅6-256
Simplify the numerator.
Tap for more steps…
Multiply 3 by 6.
b=18-256
Subtract 25 from 18.
b=-76
b=-76
Move the negative in front of the fraction.
b=-76
b=-76
The result can be shown in multiple forms.
Exact Form:
b=-76
Decimal Form:
b=-1.16‾
Mixed Number Form:
b=-116
Solve for b 3=-5/6*(-5)+b

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top